GAMBARAN MOTIVASI IBU YANG MEMILIKI BAYI USIA0-6 BULAN TENTANG PEMBERIAN ASI EKSKLUSIFDI WILAYAH POLINDES DESA SRIGADING KECAMATAN NGORO – MOJOKERTO - Khalimatus Sa?diya, Lida; Kusharyati, (JURNAL KEPERAWATAN SEHAT, 2014)
Breast milk is the first food, the main and best for the baby that is natural because milk contains a variety of nutrients is needed in the process of growth and development of the baby, there are still many among mothers with infants not exclusively breastfeding infants. This study aims to determine the motivation of mother swho had apicture of infants aged 0-6 month sof exclusive breastfeeding. The study design used a descriptive survey, the population of all mothers who have infants aged 0-6 months in the District Ngoro polindes Srigading Village of Mojokerto regency using total sampling, data collection by questionnaire and if through stages of editing, coding, scoring and tabulating. Later persentationin the form of tabulation frequency distribution. The conclusion of this study is largely motivated mothers with infants aged 0-6 months of exclusive breast feeding Midleas many. The results of this study maybe additional information and knowledge about the benefits of exclusive breastfeeding for the babys mother that motivated the motherto breastfeed her baby for 0-6 months.Keywords: Mother breastfeeding, exclusive breastfeeding, Infants 0-6 monthsof age.